P033 Long working hours and cancer risk: a multi-cohort study. (1st September 2016) - Heikkila, Katriina
Abstract : Overtime work and long working hours are associated with an increased risk of many adverse health outcomes, such as coronary heart disease and stroke. However, the relationship of excess working hours with incident cancer is unclear. To address this gap in the knowledge, we examined the association between weekly working hours and cancer risk using individual-participant data from 12 prospective studies from Denmark, Finland, Germany, Sweden, the Netherlands and the UK.Our analyses were based on data from 116 462 working men and women, who were free of cancer at study baseline. Incident cancers were ascertained from national cancer, hospitalisation and death registers. Weekly working hours were self-reported. During a follow-up ranging from 4 to 22 years, 4 371 participants were diagnosed with cancer (n colorectal cancer: 393, n lung cancer: 247, n breast cancer: 833, n prostate cancer: 534). Compared to standard working time (35–40 hours/week), working >55 hours/week was not associated with the overall cancer incidence (multivariable-adjusted HR (95% CI): 1.00 (0.85, 1.16). Similarly, working hours were unrelated to incident colorectal, lung and prostate cancers. Compared to standard hours, working >55 hours/week was associated with 1.60-fold (95% CI: 1.12–2.29) risk of female breast cancer. This association was independent of age, socioeconomic position, shift- and night-time work and lifestyle factors, but it may have been influenced by residual confounding from parity. To our knowledge, ours is the largest investigation of this topic to-date and the first to examine the association of working hours with the overall cancer risk and the risk of specific cancers. Our findings suggest that working long hours is not a risk factor for cancer in general, or lung, colorectal or prostate cancers in particular. The observed association with breast cancer would warrant further research.